Bioinspired Synthesis of Cu2+‐Modified Covalent Triazine Framework: A New Highly Efficient and Promising Peroxidase Mimic. Issue 46 (6th July 2017) - Xiong, Yuhao; Qin, Yuemei; Su, Linjing; Ye, Fanggui
Abstract: Artificial enzymes is an emerging field of research owing to the remarkable advantages of enzyme mimics over their natural counterpart, including tunable catalytic efficiencies, lower cost, ease of preparation, and excellent tolerance to variations of the reaction system. Herein, we report an efficient peroxidase mimic based on a copper‐modified covalent triazine framework (CCTF). Owing to its unique specific surface area, atomically dispersed active Cu sites, efficient electron transfer, and enhanced photo‐assisted enzyme‐like activity, the CCTF showed enhanced peroxidase‐like enzyme activity. Therefore, copper modification represents an effective route to tailor the peroxidase‐like activity of the covalent triazine frameworks. Furthermore, the mechanism of the enhanced peroxidase‐like activity and stability of the CCTF were investigated. As a proof of concept, the CCTF was used for the colorimetric detection of H2 O2 and decomposition of organic pollutants. This work provides a new strategy for the design of enzyme mimics with a broad range of potential applications. Abstract : We report an efficient peroxidase mimic based on a copper‐atom‐modified covalent triazine framework (CCTF). Owing to its unique specific surface area, atomically dispersed active Cu sites, efficient electron transfer, and enhanced photo‐assisted enzyme‐like activity, the CCTF showed enhanced peroxidase‐like enzyme activity. Therefore, copper modification presents an effective route to tailor the peroxidase‐like activity of covalent triazine frameworks.